Incumplimiento de la sentencia emitida por la Corte IDH en el caso Sarayaku vs Ecuador: un análisis a la obligación del Estado a la reparación integral. - Celi Celi, Melissa del Cisne (2023)
This thesis entitled “Failure to comply with the sentence issued by the IACHR in the case of Sarayaku vs. Ecuador: an analysis of the obligation of the State to comprehensive reparation”, refers to the existing problem that occurred after the international demand of the Kichwa Sarayaku People to the Ecuadorian State for the oil concession of a large part of its territory without prior consultation, case for which the Inter-American Court of Human Rights issued an eleven-point sentence for the State to repair the damage caused. However, after several years, the State still has not complied with three of them, for which the community filed an action for non-compliance. The objective that this research sought to reach was to carry out a conceptual, doctrinal and legal analysis of said breach and its imminent relationship with the constitutional right to comprehensive reparation. To achieve this, inductive methods and techniques such as interviews and surveys were applied that served to understand what experts on the subject consider regarding the case and to formulate the pertinent recommendations once the investigation was completed and the subject analyzed. It is in this way that, after the doctrinal and empirical analysis carried out, the conclusion has been determined the existence of non-compliance by the State with the sentence issued by the IACHR in the case of the Kichwa Sarayaku People vs. Ecuador, for which it cannot be said comprehensive reparation for the victims, which brings negative consequences to both parties, gives the State a bad international image, while the Sarayaku community remains defenseless against the human rights violations committed by the Ecuadorian State. Key words: Non-compliance, IACHR, Ecuadorian State, Sarayaku, comprehensive reparation, prior consultation, human rights.